3D fold growth rates. (25th July 2014) - Frehner, Marcel
Abstract Geological folds are inherently 3D structures; therefore, they also grow in three dimensions. Here, fold growth in all three dimensions is quantified by numerically simulating upright single‐layer folds in 3D Newtonian media. Horizontal uniaxial shortening leads to a buckling instability, which grows from a point‐like initial perturbation in all three dimensions by fold amplification (vertical), fold elongation (parallel to fold axis) and sequential fold growth (parallel to shortening direction) of secondary (and further) folds adjacent to the initial isolated fold. The two lateral directions exhibit similar averaged growth rates, leading to bulk fold structures with aspect ratios in map view close to 1. However, fold elongation is continuous with increasing bulk shortening, while sequential fold growth exhibits jumps whenever a new sequential fold appears and the bulk fold structure therefore suddenly occupies more space. Compared with the two lateral growth directions, fold amplification exhibits a slightly higher growth rate.